Efficient patient care in the digital age: impact of online appointment scheduling in a medical practice and a university hospital on the “no-show”-rate - Paola Kammrath Betancor; Daniel Boehringer; Jens Jordan; Jens Jordan; Charlotte Lüchtenberg; Marcus Lambeck; Manuel Christoph Ketterer; Thomas Reinhard; Michael Reich; Michael Reich (Frontiers in Digital Health)
BackgroundOnline appointment scheduling (OAS) increases patient satisfaction and enables more efficient care.MethodA retrospective study in an ophthalmology practice and an ophthalmology university hospital. Over 20 months, all booked practice-appointments before and after OAS implementation were recorded. Rates of cancellations/rescheduling and unexcused absences (“no-shows”) were compared. During the same period, OAS usage, no-show rates, and related factors were analyzed in the hospital.ResultsDuring the observation period, 16,894 appointments were booked in the practice and 81,173 in the hospital. In both, the rate of appointments scheduled via OAS increased continuously, with an average rate of 22.8% in the practice and 7.2% in the hospital. The no-show rate in the practice was lower for appointments booked online compared to those booked offline (median (x¯) 1.8% vs. 5.9%, p < 0.0001), whereas it was higher in the hospital (x¯ 14.3% vs. 11.2%, p < 0.0001). Regular consultations and SMS reminders were most effective in reducing no-shows in the hospital (Odds Ratio (OR) 0.40 and OR 0.93). The implementation of OAS in the practice reduced the rates of unused appointments (x¯ 22.7% vs. 10.3%, p < 0.0001) and never booked appointments (x¯ 8.6% vs. 1.6%, p < 0.0001), thereby increasing the utilization of available appointments (p < 0.0001).ConclusionOAS improves flexibility and resource use in the practice. In the hospital, SMS reminders mostly reduce no-shows, prompting development of a comprehensive reminder model.